Living donor liver transplantation for more than 30-year survived patients with native liver after Kasai operation for biliary atresia - Takashi Kobayashi (Transplantation Reports, 2020)
Objectives: A number of patients have developed liver failure after the Kasai operation for biliary atresia (BA), even after long-term postoperative course. We report our experience regarding four cases of biliary atresia required and treated with living donor liver transplantation (LDLT) during adulthood. Methods: All four patients underwent Kasai operation for BA from 1974 to 1983 and had been followed-up for more than 30 years in our institute. Then, they developed liver failure and treated with LDLT. These four patients’ records were reviewed retrospectively. All data are described using the median value. Results: Three female and one male were included. Kasai operation was performed at the age of 61 days. The type of biliary obstruction was type III-b1-ν in all. The survival period of the native liver was 440 months. The age at LDLT was 37 years. The reasons of deterioration of native liver were recurrent cholangitis in two and pregnancy and delivery in other two. The age of living donor was 40 years. Right liver grafts were used in all. Percentage of the real graft volume per standard liver volume was 47%. All patients were alive and overall graft survival rate was 100% at a follow-up period of 65 months after LDLT. Conclusion: Even after more than 30 year-survival with native liver after Kasai operation, liver failure may be caused by recurrent cholangitis or pregnancy and delivery. LDLT may be effective treatment for those adult patients if an adequate living donor is available.